Video documental :la vida de niños y adolescentes con discapacidad auditiva del Instituto Fiscal de Audición y Lenguaje Enriqueta Santillán - Caiza Lanchimba, María Ermerlinda (2015)
This work was done in order to raise awareness and changes at the social level in terms of inclusion of vulnerable groups such as people with hearing disabilities. It is intended to demonstrate a new way of seeing their daily life and their way of living, away from a sensationalist and unrealistic look. Deaf people throughout history have been considered sick people, unable to communicate. Subjecting them to inadequate education forms; from an oral stream which only marginalized and excluded them. Today, with the Plan Nacional del Buen Vivir (Ecuadorian National Plan for Good Living), the Constitution and laws such as: Ley Organica de Discapacidad (Organic Disabilities Act) have opened up a new view to the acceptance and integration of these groups in society but, through the conducted research, it is believed that the real problem is not only to deal with laws or speeches that are critical for these groups, but also with the low level of awareness of society in relation to them. The big difference between a deaf person with a hearing person is that deaf people are visual-gestural and speak with their hands and listen with their eyes while hearing people are audio-speakers; because they listen with their ears, and speak with their voice. Understanding these differences allows you to see that deaf people are a linguistic minority, whose native language like Spanish is the language of signs.